1993
DOI: 10.1073/pnas.90.2.557
|View full text |Cite
|
Sign up to set email alerts
|

Barium-induced exocytosis is due to internal calcium release and block of calcium efflux.

Abstract: The concentration of cytosolic free Ca2l ([Ca2+]J) and the release of tritiated norepinephrine ([3HJNE) were monitored during Ba2+ stimulation of sympathetic neurons cultured from chick embryos. Ba2+ (2.5 (17).Indo-1 Emission Spectra. Emission spectra of indo-1 were determined in the presence of increasing concentrations of Ca2+, Ba2+, and Ca2+ in the presence of Ba2+ by using a scanning spectrofluorometer (SPF-500C, SLM Aminco, Urbana, IL) with excitation at 355 nm and emission recorded from 360 to 550 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Importantly though, Ba 2+ is cleared one to two orders of magnitude more slowly from synaptic terminals than is Ca 2+ [38] because it is ineffectively removed from the cytoplasm by transporters including SERCA pumps [39], the NCX [24], the PMCA [40] (but see: [41]), and the MCU [24]. The ability of Ba 2+ to bind to presynaptic cytoplasmic Ca 2+ -binding proteins is less clear, although it is ineffective in activating calmodulin-like [42] or troponin-like [43] binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly though, Ba 2+ is cleared one to two orders of magnitude more slowly from synaptic terminals than is Ca 2+ [38] because it is ineffectively removed from the cytoplasm by transporters including SERCA pumps [39], the NCX [24], the PMCA [40] (but see: [41]), and the MCU [24]. The ability of Ba 2+ to bind to presynaptic cytoplasmic Ca 2+ -binding proteins is less clear, although it is ineffective in activating calmodulin-like [42] or troponin-like [43] binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ba 2+ was able to substitute for external Ca 2+ in the KCl-evoked release of [3H]5-HT. Some authors [38,48] have suggested that Ba 2+ acts directly to stimulate secretion whereas others [36] suggest that Ba 2+ acts by stimulating Ca 2+ release from intracellular stores. Our results show that unlike Ca 2+-stimulated [3H]5-HT release, Ba2+-stimulated release is only slightly affected by depletion of intracellular Ca 2+ stores with thapsigargin.…”
Section: -Ht Releasementioning
confidence: 98%
“…Ba 2+ can efficiently substitute for Ca 2+ in stimulating neurotransmitter and hormone release in several preparations such as the neuromuscular junction [43], sympathetic ganglia [26], adrenal chromaffin [12,22,23,36,38], pituitary [11] and pancreatic /3 [20,47,56] cells. In contrast to Ca 2+, Ba 2+ can also act as a secretagogue in the absence of other specific stimuli, an effect postulated to result from Ba 2+ blockade of K + channels, leading to subsequent depolarization, Ca 2+ influx and secretion [27,38].…”
Section: Introductionmentioning
confidence: 99%
“…One could speculate that Ba2+ entering the cell might directly activate the contractile ma chinery in Ca2+-free medium, as has been shown in the glycerin-treated smooth muscle of guinea-pig tenia coli [24], although there are various effects that could also contribute to the contractile response to Ba2+: the release of Ca2+ from intracellular sites and an effec tive blocking of Ca2+ extrusion [25,26].…”
Section: Influence O F Divalent Cations On the Contractile Response Omentioning
confidence: 99%